Exploring The Impact Of Social Commerce Platforms On Vocational Students' Entrepreneurial Independence: A Case Study Of Tiktok Shop - Wulandari, Sri Eka; Surbakti, Eka Wulandari; Idris, Iswandi (Jurnal Ekonomi, 2024)
This study explores the potential of social commerce platforms, specifically TikTok Shop, as a medium for enhancing entrepreneurial independence among vocational students. Using a Product Oriented-Learning approach, this research examines how TikTok Shop influences students’ entrepreneurial skills, initiative, and decision-making abilities. Data were collected from vocational students at Politeknik LP3I Medan, utilizing both quantitative surveys and qualitative interviews. The findings indicate that the Product Oriented-Learning method on TikTok Shop significantly contributes to increasing students' interest and readiness for entrepreneurship, although it shows a weaker impact on their autonomy. This study suggests integrating practical, hands-on approaches alongside TikTok Shop to fully foster entrepreneurial independence among vocational students.